CHMP6 as a novel prognostic biomarker in bladder cancer: insights from a comprehensive cell death-related gene risk model - Wei Ning; Yan-Ru Yang; Chen-Xu Wu; Yue Hou; Zhi-Wei Liu; Chang-Bin Yang (Frontiers in Oncology)
IntroductionBladder cancer (BLCA) is a prevalent and aggressive disease characterized by substantial molecular heterogeneity, complicating its diagnosis and treatment. Existing therapies, including surgery and chemotherapy, often lack specificity. Alterations in cell death mechanisms, such as ferroptosis, cuproptosis, and immunogenic cell death, significantly impact cancer progression and prognosis.MethodsWe analyzed gene expression data from TCGA and GEO. Cox regression analyses generated a prognostic risk score model incorporating LIPT1, ACSL5, and CHMP6. This model successfully stratified BLCA patients into different risk categories and was validated through survival analysis, immune infiltration, mutation burden assessment, drug sensitivity predictions, and single-cell analysis. The high-risk group was linked to differentiation processes, developmental stages, and active metabolic pathways.ResultsExperimental validation highlighted CHMP6’s role in enhancing BLCA cell survival and migration by regulating the cell cycle. The model’s prognostic relevance was further supported by drug sensitivity and immune metrics. These results provide valuable insights into potential biomarkers and therapeutic targets for BLCA treatment.DiscussionThe CHMP6 protein promotes BLCA cell survival and invasive migration through modulation of the cell cycle.